Individual factors of extending the working life for people with disabilities in Poland - Wiktorowicz, Justyna; Ziarko, Łukasz (Indywidualne czynniki wydłużające okres aktywności zawodowej osób niepełnosprawnych w Polsce, 2020)
Extending working life is an important challenge for modern economies. In Poland, 40% of people aged 50-64 are economically inactive. In the population of people with disabilities, this percentage is much higher (78%). The aim of this paper is to assess the individual factors for extending the working life of Poles aged 50-64 and their comparison between people with and without disabilities. The empirical analysis is based on the national survey, Social Diagnosis (for people aged 50-64). The analysis was carried out with the application of logistic regression, as well as the Student t-test, the Mann-Whitney test, the chi-squared test of independence. The logistic regression results show that the factors of extending working life for people with disabilities are different than for others – statistically significant determinants are formal outcomes of human capital development (regarding individuals without disabilities, the list of factors extending working life is more extensive)
Econometrics = Ekonometria, 2020, Vol. 24, No. 4, s. 1-14
Keywords: economic activity; extending working life; disability; logistic regression; aktywność ekonomiczna; wydłużanie okresu aktywności zawodowej; niepełnosprawność; regresja logistyczna